Map of “SI PANDA” Gunungsari Village, Ciranjang District, Cianjur Regency - Azriel Gifari Koswara; Muhammad Iqbal Noviandi; Nur Khalim Baihaqi (Universitas Pendidikan Indonesia, 2024)
A village is the smallest unit in a government consisting of a legal community unit that has the authority to manage its household based on original rights and customs. Peraturan Pemerintah No. 72 Tahun 2005 tentang Pemerintahan Desa, Article 14 paragraph (1) states that the village head is tasked with organizing government, development, and community affairs. Based on this, in building a village, planning is needed from various references, one of which is a village map that can be used as a component of the village information system. Village maps can be useful for village officials to find out village boundaries, and identify and inventory village potential or assets. This can be the first step in planning the empowerment of village potential. The map made by UPI KKN students in Gunungsari Village is the